2019
DOI: 10.1186/s12905-019-0858-3
|View full text |Cite
|
Sign up to set email alerts
|

Determinant of time-to-first birth interval after marriage among Ethiopian women

Abstract: BackgroundTime-to-first birth after marriage has a significant role in the future life of each individual woman and has a direct relationship with fertility. This study aimed to see the determinant of time-to-first birth interval after marriage among Ethiopian women.MethodsThe data was obtained from 2011 Ethiopia Demographic and Health Survey which is the third survey. The sample was selected using a stratified; two-stage cluster sampling design and the data was analysed using parametric shared frailty model.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 12 publications
(12 reference statements)
5
14
0
Order By: Relevance
“…The results of this model concluded that age at first marriage and education were the factors that had a significant effect on age at first giving birth. These results are in line with similar studies conducted in Ethiopia (Chernet et al 2019) and in Nigeria (Fagbamigbe and Idemudia, 2016). The study concluded that the younger a woman married, the earlier the age of first giving birth.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of this model concluded that age at first marriage and education were the factors that had a significant effect on age at first giving birth. These results are in line with similar studies conducted in Ethiopia (Chernet et al 2019) and in Nigeria (Fagbamigbe and Idemudia, 2016). The study concluded that the younger a woman married, the earlier the age of first giving birth.…”
Section: Discussionsupporting
confidence: 92%
“…The results of research conducted by Fagbamigbe and Idemudia (2016) show that the time of marriage and education are the most significant factors affecting the age of first giving birth. A similar study was conducted by Chernet, Shebeshi, and Banbeta (2019) regarding the determinants of the interval for first giving birth after marriage among Ethiopian women. The results showed age, place of residence, employment status, contraceptive use, and education of women were significantly associated with the age of first giving birth (Chernet et al, 2019).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Bangladeshi (1) and results elsewhere (3,4,7,14,19,21,22,26,(31)(32)(33)(34)(35)(41)(42)(43). In particular, ensuring those adolescent girls to receive at least a secondary level of education is the optimal way of delaying childbirth (53,58).…”
Section: Discussionmentioning
confidence: 99%
“…Childbirth is being delayed to a later age with the mean age at rst birth 26.3 years in the United States America (USA) (39) to 30 years in Britain (3). The majority works of the literature revealed that the use of any contraception delay age at rst birth (5,8,9,(23)(24)(25)30,(40)(41)(42).…”
mentioning
confidence: 99%